Antigen 85 complex as a powerful Mycobacterium tuberculosis immunogene: Biology, immune-pathogenicity, applications in diagnosis, and vaccine design. (November 2017) - Karbalaei Zadeh Babaki, Mohsen; Soleimanpour, Saman; Rezaee, Seyed Abdolrahim
Abstract: Mycobacterium tuberculosis ( Mtb ) is one of the most life-threatening mycobacterial species which is increasing the death rate due to emerging multi-drug resistant (MDR) strains. Concerned health authorities worldwide are interested in developing an effective vaccine to prevent the spread of Mtb . After years of research, including successful identification of many Mtb immunogenic molecules, effective therapeutic agents or a vaccine have yet to be found. However, among the identified Mtb immunogenes, antigen 85 (Ag85) complex (Ag85A, Ag85B, and Ag85C) is receiving attention from scientists as it allows bacteria to evade the host immune response by preventing formation of phagolysosomes for eradication of infection. Due to their importance, A85 molecules are being utilized as tools in diagnostic methods and in the construction of new vaccines, such as recombinant attenuated vaccines, DNA vaccines, and subunit vaccines. This paper represents a comprehensive review of studies on Mtb molecules examining pathogenicity, biochemistry, immunology, and the role of Mtb in therapeutic or vaccine research.